Polypodiales a promising fern order as a source of anticancer agent: A comprehensive review - Dwi K. PRATOKO; Triana HERTIANI; Ari S. NUGRAHA; Puji ASTUTI (Notulae Botanicae Horti Agrobotanici Cluj-Napoca)
Ferns are vascular plants that have been extensively studied in recent decades for their phytochemical and anticancer activities. Polypodiales is an order of ferns consisting of 26 families with more than 9600 species (>80% of the total number of fern species). There have been many reports on the potential activity of plants and their phytochemicals that belong to the Polypodiales order in the search for anticancer agents. However, until now, there has been no comprehensive review of the anticancer activity of ferns, specifically in the order. This research is based on a thorough analysis of relevant literature in Scopus and PubMed databases from 1979 to 2022. The literature search used specific keywords, with criteria for this review appropriate for cell-based experiments and molecular mechanisms of anticancer activity. In vivo assay, chemopreventive or cytoprotective activity, and testing of combinations of plants or compounds were excluded. A total of 66 species were distributed in 11 families of the order Polypodiales, were summarized, constructed and discussed the traditional use, pharmacology, and phytochemicals associated with anticancer properties. The comprehensive research study showed that plants of the order Polypodiales and their phytochemicals exhibit anticancer effects against various cancers. Pteridaceae is a family that contains the most anticancer bioactive compounds. ent-11α-hydroxy-15-oxo-kaur-16-en-19-oic acid (5F), terpenoid from Pteridaceae family exhibits promising against colorectal, gastric, hepatocellular, lung, laryngeal, nasopharyngeal, and breast cancer cell lines. The ability to induce apoptosis through several pathways that can activate the mitochondrial-mediated apoptosis pathway, such as inhibiting the NF-kB pathway and increasing ROS formation. Further research is needed to explore more ferns, reveal their active compounds activity and mechanism of action, and conduct in vivo assay to confirm their efficacy and safety for the development of cancer treatment.